( n + 1 ) ( n 3 1 ) (n+1) \mid (n^3-1)

Find the total number of integers n n such that ( n + 1 ) ( n 3 1 ) . (n+1) \mid (n^3-1).


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Note first that n 3 1 = ( n + 1 ) 3 3 n 2 3 n 2 = ( ( n + 1 ) 2 3 n ) ( n + 1 ) 2 n^{3} - 1 = (n + 1)^{3} - 3n^{2} - 3n - 2 = ((n + 1)^{2} - 3n)(n + 1) - 2 .

Now clearly n = 1 n = -1 is not a solution since 0 0 does not divide 2 2 , so dividing through by n + 1 n + 1 yields

n 3 1 n + 1 = ( ( n + 1 ) 2 3 n ) 2 n + 1 \dfrac{n^{3} - 1}{n + 1} = ((n + 1)^{2} - 3n) - \dfrac{2}{n + 1} ,

which will be an integer whenever ( n + 1 ) 2 (n + 1)|2 . Since the divisors of 2 2 are just ± 1 \pm 1 and ± 2 \pm 2 , there are a total of 4 \boxed{4} possible values of n n , namely 3 , 2 , 0 -3,-2,0 and 1 1 .

Exactly the same way. Great job!

Jun Arro Estrella - 4 years, 5 months ago
Sharky Kesa
Jan 2, 2017

Note that n 3 + 1 = ( n + 1 ) ( n 2 n + 1 ) n^3 + 1 = (n+1)(n^2 - n + 1) , so n + 1 n 3 + 1 n+1 \mid n^3 + 1 . We now have the following

n + 1 n 3 1 n + 1 n 3 + 1 n + 1 ( n 3 + 1 ) ( n 3 1 ) = 2 \begin{aligned} n+1 &\mid n^3 - 1\\ n+1 &\mid n^3 + 1\\ \implies n+1 &\mid (n^3+1)-(n^3-1)=2\\ \end{aligned}

Therefore, n + 1 2 n+1|2 . The factors of 2 are 2 , 1 , 1 , 2 -2, -1, 1, 2 , which gives the values of n n as 3 , 2 , 0 , 1 -3, -2, 0, 1 . Therefore, there are 4 different integers which satisfy.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...